The landscape of perioperative nursing education in Africa: a scoping review - Wong, Maddie; Banda, Zione; Nabulime, Josephine; Matunda, Nira; Nkangala, Edina; Silvers, Rebecca (Frontiers in Medicine, 2024)
Background Not everyone across the globe has access to safe surgical care. There exist stark disparities in surgical mortality between high-income and low-and middle-income countries. Quality perioperative care across the surgical care continuum can mitigate these disparities. Nurses play a vital role in providing quality perioperative care and their competency in perioperative nursing directly impacts surgical outcomes. Across Africa, formal educational opportunities for nurses in perioperative care is not well understood. Methods This is an informal scoping review of the existing literature investigating the current state of perioperative nursing education across the African continent. Ten articles were included in the analysis. Results Few programs exist across Africa that provide specialized training for nurses in perioperative medicine. Programs that have been formally evaluated show improved knowledge and clinical skills among nurses. Conclusion Greater research is necessary to establish a more robust evidence base in support of increasing access to perioperative nursing education to improve patient outcomes. Obstacles remain to designing, implementing, and evaluating new educational programs.